Investigation of Damage Caused by Chlorine-Contaminated Fuel in Standard Vehicle Components - Vincenzo La Battaglia; Valerio Mussi; Stefano Marini; Alessandro Giorgetti (Engineering Proceedings, 2025)
Several car manufacturers have encountered corrosion in certain mechanical components caused by chlorine in fuel. The current regulations governing the quality of fuel allowed for trade are briefly described. Next, this paper analyzes the possible origin of chlorine in damaged components. In particular, the phenomenon of corrosion found in EGR valves and EGR coolers is analyzed. The analyses conducted to determine the nature of the corrosion and its origin are illustrated. Finally, the effects of the phenomenon on engine operation are analyzed, depending on the type of damaged component.